45th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2009
DOI: 10.2514/6.2009-4890
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study and Demonstration of an Aluminum and Ice Solid Propellant

Abstract: Aluminum-water reactions have been proposed and studied for several decades for underwater propulsion systems and applications requiring hydrogen generation. Aluminum and water have also been proposed as a frozen propellant, and there have been proposals for other refrigerated propellants that could be mixed, frozen in situ, and used as solid propellants. However, little work has been done to determine the feasibility of these concepts. With the recent availability of nanoscale aluminum, a simple binary formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In the current investigation, the performance and viability of nAl and ice (ALICE), and various ALICE based propellant formulations were examined. Safety tests such as ESD, mechanical tensile tests, and impact tests have been performed [25]. Both fundamental steady-state strand-burner experiments and applied lab-scale hot-fire motor experiments were employed to ascertain ballistic data.…”
Section: Nano Aluminum-ice (Alice) Based Propellantsmentioning
confidence: 99%
“…In the current investigation, the performance and viability of nAl and ice (ALICE), and various ALICE based propellant formulations were examined. Safety tests such as ESD, mechanical tensile tests, and impact tests have been performed [25]. Both fundamental steady-state strand-burner experiments and applied lab-scale hot-fire motor experiments were employed to ascertain ballistic data.…”
Section: Nano Aluminum-ice (Alice) Based Propellantsmentioning
confidence: 99%
“…17,18 However, most of studies had focused on the investigation of the reaction of aluminum and water at low temperature, [19][20][21] and the combustion behaviors of aluminum/ice solid propellant. [22][23][24] Only a few experimental studies were carried out on the combustion characteristics of aluminum in heated steam atmosphere. 25,26 Based on thermogravimetric analysis, Schoenitz et al 27 found that the oxidation process of aluminum powder in steam atmosphere was similar to that in oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen nano-aluminum and water (ALICE) has been researched recently as a propellant [2,3,[11][12][13][14][15]. Burning rate and combustion efficiency experiments on aluminum and water propellants containing 38 nm aluminum powder have been reported [2,3,16].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, nAl/H 2 O mixtures are insensitive to impact ignition, having an ignition threshold in excess of 2.2 m. Propellants containing 80 nm or larger average particle size aluminum were also found to be insensitive to shock initiation. [3,12,13]. In exploring the effects of particle size variation, Risha et al [3] found that the burning rate is predominantly a function of aluminum particle diameter.…”
Section: Introductionmentioning
confidence: 99%